2020
DOI: 10.3390/su12062463
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Supplementation with Moringa oleifera Leaves and/or Seeds Powder on Production, Egg Characteristics, Hatchability and Blood Chemistry of Laying Japanese Quails

Abstract: The present study aimed to evaluate the effect of dietary Moringa oleifera (M. oleifera) leaves and/or seed powder on laying Japanese quail performance in terms of egg production, egg quality, blood serum characteristics, and reproduction. In total, 168 Japanese quails (120 hens and 48 males) at eight weeks of age in laying period were randomly distributed to four treatment groups, with six replicates per group and seven birds (five hens and two males) per replicate. The first group (G1) served as a control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
38
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 20 publications
7
38
1
1
Order By: Relevance
“…This replenishing of GSH may be responsible for the regaining of GPx and GST activity. The antioxidant capacity of MO has already been reported in some investigations; Onah et al, [32] concluded that supplementation of MO extracts is associated with a significant improvement in the levels of both liver and kidney GST, SOD, and CAT during lead acetate intoxication in fish [33]. Similarly, Uma et al [34] and Fakurazi et al [35] showed that MO leaves protected against acetaminophen-induced liver damage by decreasing liver enzymes and hepatic lipid peroxidation as well as increasing antioxidant enzyme levels.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This replenishing of GSH may be responsible for the regaining of GPx and GST activity. The antioxidant capacity of MO has already been reported in some investigations; Onah et al, [32] concluded that supplementation of MO extracts is associated with a significant improvement in the levels of both liver and kidney GST, SOD, and CAT during lead acetate intoxication in fish [33]. Similarly, Uma et al [34] and Fakurazi et al [35] showed that MO leaves protected against acetaminophen-induced liver damage by decreasing liver enzymes and hepatic lipid peroxidation as well as increasing antioxidant enzyme levels.…”
Section: Discussionmentioning
confidence: 81%
“…It is characterized by resistance to diseases, fast growth, and easy adaption to commercial diets [30]. Several studies were performed to evaluate the importance of medicinal plants' leaf extracts for detoxification of polluted ecosystems [31][32][33][34][35], promote fish growth [36], and improve resistance against toxicity. However, in one recent study which has evaluated the ameliorative effect of MO leaf extract against sodium fluoride (NaF) in sea bream via the estimation of liver function, catalase, and superoxide dismutase activity [37], the authors concluded an efficient hepatoprotective and antioxidant effect of MO leaf extract.…”
Section: Introductionmentioning
confidence: 99%
“…Phytogenic additives are used in poultry production as natural feed additives to enhance the growth rate and productive performance. Beneficial impacts of herbs in poultry feeding such as improvement feed intake, appetite, energising secretion of digestive enzyme, stimulation immune response and antioxidant, antimicrobial, antihelminthic, antiviral properties and anti-heat stress modulators (Shewita and Taha 2018;Alagawany et al 2019Gado et al 2019;Khafaga et al 2019;Hafez and Attia 2020;Abd El-Hack, Alagawany et al 2020;Abd El-Hack, Abdelnour et al 2020;Ashour, Bin-Jumah et al 2020;Ashour, El-Kholy et al 2020;Batiha et al 2020). Several studies reported useful impacts of phytogenic additives on growth performance, nutrient retention, gut health, intestinal microflora, reduced the susceptibility to diseases, enhanced immunity function and improved carcass traits in broiler chickens (Ashour et al 2014;Abd El-Hack and Alagawany 2015;Taha et al 2019;Abo Ghanima et al 2020;Ashour, Bin-Jumah et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is rich in flavonoids, carotenoids, tocopherols, selenium, and vitamin E [22,23] and has a potent antioxidant activity [24,25]. In addition, Ashour et al [26] reported significantly increased egg production and improved hatchability, along with some egg quality parameters, and also lowered some blood biochemical components in Japanese quail that were fed an M. oleifera seeds-supplemented diet. Additionally, Lan et al [27] revealed that supplementation of Moringa leaf powder at 5% had no effect on the performance of laying quail but remarkably enhanced yolk color.…”
Section: Introductionmentioning
confidence: 99%